A principal-agent model of sequential testing - Dino Gerardi; Lucas Maestri (Theoretical Economics, 2012)
This paper analyzes the optimal provision of incentives in a dynamic information acquisition process. In every period, the agent can acquire costly information that is relevant to the principal's decision. Each signal may or may not provide definitive evidence in favor of the good state. Neither the agent's effort nor the realizations of his signals are observable. First, we assume that the agent has no private information at the time of contracting. Under the optimal mechanism, the agent is rewarded only when his messages are consistent with the state. The payments that the agent receives when he correctly announces the good state increase over time. We then characterize the optimal mechanisms when the agent has superior information about the state at the outset of the relationship. The principal prefers to offer different contracts if and only if the agent types are sufficiently diverse. Finally, all agent types benefit from their initial private information.
Keywords: C72; D82; D83; 330; Dynamic mechanism design; information acquisition; sequential testing